Avaliação química e biológica em diferentes estádios de maturação da casca e polpa do fruto de A. edulis - DA ROSA, Juliano Santos; DE CASTRO, Thiago Luis Aguayo; MASCARENHAS, Maria do Socorro; CARDOSO, Claudia Andrea Lima (ANAIS DO ENIC, 2025)
-